Methodological considerations in studying digestive system physiology in octopus: limitations, lacunae and lessons learnt - Andrews, Paul L. R.; Ponte, Giovanna; Rosas, Carlos (Frontiers in Physiology, 2022)
Current understanding of cephalopod digestive tract physiology is based on relatively “old” literature and a “mosaic of data” from multiple species. To provide a background to the discussion of methodologies for investigating physiology we first review the anatomy of the cephalopod digestive tract with a focus on Octopus vulgaris, highlighting structure-function relationships and species differences with potential functional consequences (e.g., absence of a crop in cuttlefish and squid; presence of a caecal sac in squid). We caution about extrapolation of data on the digestive system physiology from one cephalopod species to another because of the anatomical differences. The contribution of anatomical and histological techniques (e.g., digestive enzyme histochemistry and neurotransmitter immunohistochemistry) to understanding physiological processes in discussed. For each major digestive tract function we briefly review current knowledge, and then discuss techniques and their limitations for the following parameters: i) Measuring motility in vitro (e.g., spatiotemporal mapping, tension and pressure), in vivo (labelled food, high resolution ultrasound) and aspects of pharmacology; ii) Measuring food ingestion and the time course of digestion with an emphasis on understanding enzyme function in each gut region with respect to time; iii) Assessing transepithelial transport of nutrients; iv) Measuring the energetic cost of food processing, impact of environmental temperature and metabolic rate (flow-through/intermittent respirometry); iv) Investigating neural (brain, gastric ganglion, enteric) and endocrine control processes with an emphasis on application of molecular techniques to identify receptors and their ligands. A number of major knowledge lacunae are identified where available techniques need to be applied to cephalopods, these include: i) What is the physiological function of the caecal leaflets and intestinal typhlosoles in octopus? ii) What role does the transepithelial transport in the caecum and intestine play in ion, water and nutrient transport? iii) What information is signalled from the digestive tract to the brain regarding the food ingested and the progress of digestion? It is hoped that by combining discussion of the physiology of the cephalopod digestive system with an overview of techniques and identification of key knowledge gaps that this will encourage a more systematic approach to research in this area.